The Power of the Concubine in Selected Traditional Malay Historiographical Literary Works: (Kekuasaan Gundik dalam Teks Historiografi Sastera Melayu Terpilih) (Malay Literature, 2019)
This study discusses the role of the concubine in selected traditional Malay literature, specifically Sulalatus Salatin, Hikayat Rajaraja Pasai and Hikayat Patani, as these three works highlight several episodes that involve concubines, compared to other historiographical literary works. The objective of this study is to focus on concubine characters, which are seldom given attention or considered insignificant even though they have left a definite impact in specific situations. The concubine character will be discussed in terms of her power and role in the palace of the olden days. The study will also apply the theory of power as propounded by Lukes (1977) in analysing the role and concept of the concubine as put forth by Ismail Azman (2009). The significance of this study is the focus on the concubine character, which has been overlooked in favour ofother main characters such as the king, the queen and the high official, among others. The concubine character in fact has her own standing, to the extent of impacting a particular government or state.Keywords: Concubine, role and power, traditional Malay literature